Eugenol and tricaine methanesulfonate as anhestesics for the pearl cichlid - Honorato, Luan (2021)
Anesthesia reduces the handling process duration and prevent fish injuries. The anesthetic effect and ideal concentrations of eugenol and tricaine methanesulfonate (MS-222) were tested for pearl cichlid (Geophagus brasiliensis) juveniles with an average weight of 4.4 g in water at 24ºC. The criterion for determining the optimal dose considered an induction time of one minute. Experiment 1 tested the concentrations of 25, 75, 150 and 300 mg L-1 of eugenol. The best results were obtained at doses of 150 and 300 mg L-1. Experiment 2 aimed to establish a more accurate result by testing the concentrations of 180, 210, 240 and 270 mg L-1, and led to an estimation of 217 mg L-1 of eugenol to induce anesthesia in one minute. Experiment 3 evaluated 200, 300, 400, 500 and 600 mg L-1 of tricaine, of which the concentration of 294 mg L-1 was estimated to induce anesthesia in one minute. No significant differences were observed for recovery times when using either of the anesthetics. No mortality was observed within 24 hours after the experiments for any concentration of the anesthetics. The present study recommends 217 mg L-1 of eugenol or 394 mg L-1 of tricaine for anesthesia of the pearl cichlid.